Epidemiology, Risk Factors and Outcome Due to Multidrug Resistant Organisms in Paediatric Liver Transplant Patients in the Era of Antimicrobial Stewardship and Screening - Anita Verma; Sunitha Vimalesvaran; Anil Dhawan (MDPI AG, 2022)
(1) Background: Multidrug-resistant organisms (MDRO) are a growing problem in liver transplant recipients (LTR), associated with high morbidity and mortality. We reviewed the impact of antimicrobial stewardship (AMS) and active screening of MDRO on the epidemiology and outcomes in paediatric LTR. (2) Methods: Single-centre retrospective review of paediatric LTR from January 2017 to December 2018. (3) Results: Ninety-six children were included; 32 (33%) patients were colonised with ≥1 MDRO and 22 (23%) patients had MDRO infections. Median (IQR) duration for start of infection was 9.5 (1.8-16.0) days. Colonisation rate with Gram-positive MDRO was 15.6%, with infection rate of 6.2%; majority due to Vancomycin-Resistant Enterococcus faecium (VRE). Colonisation with Gram-negative MDRO was 27.0%, with infection rate of 16.6%; majority due to extended-spectrum β-lactamase producing Enterobacteriaceae. Colonisation and infection rate due to Carbapenem-resistant Enterobacteriaceae was 6% and 3%, respectively, during screening and AMS, compared to historical control of 25% and 30%, respectively, without screening and AMS. There was significant reduction in VRE and CRE infection during AMS period in comparison to historical control. Pre-transplant risk factors including bacterial infections pre-transplant (p < 0.01), diagnosis of biliary atresia (p = 0.03), exposure to antibiotics (p < 0.01), EBV viraemia (p = 0.01), and auxiliary transplantation (p < 0.01) were associated with post-transplant MDRO infections. Patients with MDRO infections had longer length of hospital and paediatric intensive care unit stay days (p < 0.01) but associated with no mortality. (4) Conclusions: Our results demonstrate low incidence of colonisation and infections with MDRO, which were associated with high morbidity but no mortality in paediatric LTR. There was significant reduction in MRSA, VRE, and CRE during AMS period compared to pre-AMS era. Some risk factors are unavoidable but antibiotic overuse, early initiation of appropriate antibiotic therapy and effective infection prevention strategies can be monitored with multifaceted approach of AMS and screening of MDRO. With limited therapeutic options for MDRO and efficacy data of newer antibiotics in paediatric LTR, robust infection control practices are of paramount importance.